2019
DOI: 10.35940/ijitee.a4956.119119
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance of Steel Frames with Inverted V-Braces for North Cyprus

Abstract: Cyprus Island is located in a high-risk zone, in which the buildings should have lateral load-resistance systems to resist the lateral imposed loads. Bracings play a vital role in the structural behavior of buildings during an earthquake. There are many bracing systems that can be found thorough searching in the literature. However, there are insufficient studies regarding the inverted-V bracing system in accordance with the Northern Cyprus seismic code of NCSC-2015. In this study, the seismic performance of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…From table 11 explains the effectivity various bracing which the effectiveness of the Inverted V brace is more than the V brace. It can be concluded that Inverted V brace is more effective than V brace [30], [31].…”
Section: B Story Drift Resultsmentioning
confidence: 93%
“…From table 11 explains the effectivity various bracing which the effectiveness of the Inverted V brace is more than the V brace. It can be concluded that Inverted V brace is more effective than V brace [30], [31].…”
Section: B Story Drift Resultsmentioning
confidence: 93%
“…The numerical analysis of the unbraced EBF results proposes that the seismic design provisions specified in CSA S16 for the conventional EBFs be revisited to address the potential instability in these structures. Alkhattab [26] mentioned in his study that the objective is to look at how different kinds of inverted V-bracing systems affect the seismic performance of steel-framed structures in the city of Famagusta in Cyprus. To accomplish this goal, 20 models of steel frame buildings and 4 different bracing methods.…”
Section: Factors Affecting the Bracing System 31 The Type Of Bracingmentioning
confidence: 99%